Feminine/Feminist: A Poststructural Reading of Relational Learning in Women's Social Action Organizations - Leona M. English (Adult Education Research Conference, 2004)
This paper reports on research with 8 board members and 8 directors of women’s social action organizations. A poststructural reading of the data gives voice to an under theorized aspect of humanist relational learning in women’s organizations and makes visible the power-relationships. It explores women’s learned practices of resistance, and offers a paradoxical view of relational learning on social action that attends to the ethic of care as well as to power relations.